Description of Metriaclima koningsi, a new species (Teleostei: Cichlidae) from Lake Malaŵi, Malaŵi, Africa - Stauffer, Jay R., Jr. (Zootaxa, 2018)
A new species, Metriaclima koningsi, is described from Likoma and Maingano islands in Lake Malaŵi. The species is distinguished from other congeners, except Metriaclima usisyae Li, Konings & Stauffer, by the absence of conspicuous bars along its flank and the presence of a dark submarginal band in the dorsal fin. Males of M. usisyae have gold coloured flanks, while males of M. koningsi have blue flanks.